Comparison of Fine Aggregate to Mortar Strength Between Sand Awang Bangkal and Sand Barito - Khairil Yanuar; Abdul Hafizh Ihsani; Muhammad Arya Anugerah; Ruspiansyah Ruspiansyah (Journal of Business Social and Technology, 2023)
The progress of building construction that is developing in our country affects the number of diverse building functions resulting in the quantity of buildings, the acceleration of the desired building and the demand for higher quality construction. Mortar is a mixture consisting of Cement, Fine Aggregate and Water. The adhesive in the mortar can be in the form of clay, lime, or cement. Fine Aggregate (Sand) in the mortar mix serves as a filler (glued material) either in a hardened or unhardened state. This final project research was conducted at the Structure and Materials Laboratory of the Banjarmasin State Polytechnic. Data collection was carried out by the method used to collect, study and collect data or sources related to the topic raised in a study. Studies can be obtained from various sources, such as journals, papers, reports, documentation books, internet (browsing) and libraries. The results of the compressive strength on the age of mortar At the age of 3 days Semen Gresik Pasir Barito is 6.05 Mpa, At the age of 7 days Semen Gresik Pasir Barito is 6.05 Mpa, At the age of 14 days Semen Gresik Pasir Awang Bangkal is 8.66 Mpa, At the age of 28 days Semen Gresik sand Awang Bangkal 10.68 MPa. It can be concluded that Pasir Barito is included in zone IV and Pasir Awang Bangkal is included in zone II. Based on the results of the average compressive strength of the mortar, the results obtained were: Barito sand at the age of 3 days was 6.05 Mpa, at 7 days old was 6.05 Mpa, aged 14 days was 7.68 Mpa, and aged 28 days was 9.56 Mpa, Pasir Awang Bangkal at the age of 3 days was 4.14 Mpa, the age of 7 days was 4.75 Mpa, the age of 14 days was 8.66 Mpa, and the age of 28 days was 10.68 Mpa.